Controlling pH in shake flasks using polymer-based controlled-release discs with pre-determined release kinetics - Scheidle, Marco (BioMed Central, 2011)
BACKGROUND: There are significant differences in the culture conditions between small-scale screenings and large-scale fermentation processes. Production processes are usually conducted in fed-batch cultivation mode with active pH-monitoring and control. In contrast, screening experiments in shake flasks are usually conducted in batch mode without active pH-control, but with high buffer concentrations to prevent excessive pH-drifts. These differences make it difficult to compare results from screening experiments and laboratory and technical scale cultivations and, thus, complicate rational process development. In particular, the pH-value plays an important role in fermentation processes due to the narrow physiological or optimal pH-range of microorganisms. To reduce the differences between the scales and to establish a pH-control in shake flasks, a newly developed easy to use polymer-based controlled-release system is presented in this paper. This system consists of bio-compatible silicone discs embedding the alkaline reagent Na(2)CO(3). Since the sodium carbonate is gradually released from the discs in pre-determined kinetics, it will ultimately compensate the decrease in pH caused by the biological activity of microorganisms. RESULTS: The controlled-release discs presented here were successfully used to cultivate E. coli K12 and E. coli BL21 pRSET eYFP-IL6 in mineral media with glucose and glycerol as carbon (C) sources, respectively. With glucose as the C-source it was possible to reduce the required buffer concentration in shake flask cultures by 50%. Moreover, with glycerol as the C-source, no buffer was needed at all. CONCLUSIONS: These novel polymer-based controlled-release discs allowed buffer concentrations in shake flask media to be substantially reduced or omitted, while the pH remains in the physiological range of the microorganisms during the whole cultivation time. Therefore, the controlled-release discs allow a better control of the pH, than merely using high buffer concentrations. The conditions applied here, i.e. with significantly reduced buffer concentrations, enhance the comparability of the culture conditions used in screening experiments and large-scale fermentation processes.